SOLUTIONS FOR APPLYING THE EDUCATIONAL TECHNOLOGY IN VIETNAMESE VOCATIONAL EDUCATION INSTITUTIONS - Bui, Van Hong (Advances in Social Sciences Research Journal, 2019)
In the context of growing science and technology, increasing knowledge, more diverse learning needs of learners and especially the trend of international integration in vocational education as at present, the ability to apply technology and innovate teaching methods in training plays a decisive role to the quality of human resource training. Based on the analysis of the impact of the Fourth Industrial Revolution (Industry 4.0) on the vocational education system and the trend of innovation in human resource training in vocational education institutions in Vietnam, the article proposes solutions for applying educational technology in training at the vocational education institutions, meeting the needs of innovation and improving the quality of Vocational Education today